Dental biomaterials for chairside CAD/CAM: State of the art - Lambert, Hugo (J Adv Prosthodont, 2017)
The wide use of chairside CAD/CAM restorations has increased the diversity of the restorative material. For the practitioner, the selection of the appropriate material is difficult amongst the variety offered by the market. Information on the characteristics of the products can be difficult to assess due to the lack of up-to-date classification and the lack of reliability of manufacturer's advertising. The purpose of this article is to structure the data on restorative materials provided by various sources in order for the practitioner to choose the product most suited to the clinical situation. The objective is to classify chairside CAD/CAM materials and to define their characteristics and indications.